A Zero-Trust Authentication Scheme With Access Control for 6G-Enabled IoT Environments - Seunghwan Son; Deokkyu Kwon; Sangwoo Lee; Hyeokchan Kwon; Youngho Park (IEEE Access)
The sixth generation (6G) is the next generation of wireless communication technology, is not limited to cellular networks but can be used to provide better services in all areas of wireless communication, including vehicles, drones, and smart homes. However, these advancements in 6G technology require further security considerations. In earlier networks, authentication schemes were designed to rely on a secure channel between the core network and access points. The 6G network is an open, distributed network that integrates multiple domains and entities and cannot guarantee secure channels in the network. The 6G network requires a new security authentication scheme that applies the zero-trust model. Therefore, this study proposes a zero-trust authentication scheme with access control for 6G-enabled Internet of Things environments. The scheme uses blockchain technology for mutual authentication in a distributed environment and lightweight attribute-based encryption to ensure dynamic access control and network efficiency. This study compares the proposed authentication method with existing methods and demonstrates that this scheme has better performance and security. To the best of our knowledge, this paper is the first to propose a specific authentication protocol with access control considering the zero-trust model in a 6G environment.